Shelf life - Man, C. M. Dominic (Hoboken, NJ : Wiley-Blackwell, 2015)
'Encompasses the core considerations about shelf life. Section 1 introduces shelf life, describes its relationship to food safety, and provides answers to the frequently asked questions around shelf life determination and testing which are a manager's chief concerns. Section 2 covers the science of the various ways in which food deteriorates and spoils, including the physical, chemical and microbiological changes. Section 3 looks at shelf life in practice, using case studies of different products to illustrate how shelf life may be determined in real life settings'--
Machine generated contents note: Preface to the Second Edition Preface to the First Edition Section 1 Introduction to Shelf Life of Foods -- Frequently Asked Questions 1.1 What is shelf life? 1.2 Why are food safety and shelf life related? 1.3 Who should be interested in shelf life of foods? 1.4 Who is responsible for determining shelf life? 1.5 Is it illegal to give a wrong shelf life to a food product? 1.6 How long a shelf life should my product have? 1.7 What is accelerated shelf life testing? 1.8 What are the resources required for determining shelf life? 1.9 How is the end of shelf life normally decided? 1.10 How do we ensure that the shelf lives established for our products are accurate and reproducible 1.11 Can mathematical/computer models help in shelf life determination? 1.12 What is challenge testing? 1.13 Can the shelf life of my product be extended? 1.14 How are storage tests and trials set up for determining shelf life? 1.15 Food waste and shelf life: What is the problem? 1.16 Summary Section 2 The Ways Food Deteriorates and Spoils 2.1 Mechanisms of food deterioration and spoilage 2.2 Factors influencing the shelf life of foods 2.3 Summary Section 3 Determining Shelf Life in Practice 3.1 Case study 1 -- chilled recipe dish 3.2 Case study 2 -- savoury potato snack 3.3 Case study 3 -- carbonated soft drink 3.4 Case study 4 -- condiment sauce 3.5 Case study 5 -- frozen baked cake 3.6 Summary Epilogue Appendix A: The Arrhenius Model Appendix B: The CIMSCEE Formulae for Microbiological Safety and Stability References Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Food -- Storage; Food -- Shelf-ife dating